(untitled) (Vietnam Journal of Community Medicine, 2026)
Two patients had hyperparathyroidism syndrome due to primary parathyroid tumor, located in the mediastinum, so it was detected when complications had already occurred. After entering the Thoracic Surgery Department of Bach Mai Hospital, the patient was examined: ultrasound, computed tomography, magnetic resonance imaging and parathyroid scintigraphy, which determined the parathyroid tumor was located in the mediastinum. Endoscopic mediastinal parathyroid tumor was performed for 1 case, and open mediastinal surgery for the other case. Postoperative results progressed well, PTH (Parathyroid Hormone) and other indicators returned to normal.